Temperature integrity and exposure to freezing temperature during vaccine transfer under the universal immunization program in Three States of India - Manoja Kumar Das; Narendra Kumar Arora; Thomas Mathew; Bhadresh Vyas; Monica Sindhu; Abhishek Yadav (Wolters Kluwer Medknow Publications, 2019)
Temperature excursion and exposure to sub-zero temperatures may reduce the potency of the freeze-sensitive vaccines. This study assessed temperature during vaccine transfers at various levels under the Universal Immunization Program. This cross-sectional study undertaken in 21 districts of three states of India - Bihar (n = 8), Kerala (n = 8), and Gujarat (n = 5). We documented temperature inside the cold boxes and vaccine carriers using LogTag-Trix8 data loggers. In total, 110 vaccine transportation episodes were observed; 55 inter-facility transfers and 55 outreach sessions. Sizable proportions of inter-facility (9% to 35%) and outreach vaccine transfers (18%) were exposed to sub-zero temperature. The proportions of exposure to temperature to >8°C were in the range of 0.8%-11.3% for inter-facility transfers and 2.3% for outreach sessions. The vaccines were exposed to freezing temperatures for significant durations during transportation across the cold chain. Rigorous monitoring of temperature integrity is essential to ensure the delivery of potent vaccines and to avoid vaccine failure.